PENGARUH MODAL PSIKOLOGIS DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU DIMODERASI GAYA KEPEMIMPINAN TRANSFORMASIONAL PADA SMK NEGERI DI KABUPATEN PEMALANG (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study is about the effects of psychological capital and organizational commitment on teacher performance moderated transformational leadership style at SMK in Pemalang regency. The purpose of this study is to examine how the influence of psychological capital and organizational commitment on teacher performance moderated transformational leadership style. The population in this study are 133 SMK’s teachers in Pemalang regency. The research data in this research is primary data which conducted  by using questionnaire. The data analysis based on  Moderation Regression Analisys (MRA) type quasi moderator. The results showed that psychological capital did not effect on the teacher performance. Organizational commitment have a positive effect  on the teacher performance. Transformational leadership style have a positive effect  on the teacher performance. Transformational leadership style did not moderate the influence of psychological capital to the teacher performance. Transformational leadership style did not moderate the influence of organizational commitment to the teacher performance.Keywords: Psychological Capital, Organizational Commitment, Transformational Leadership Style, Teacher Performance